Awe of What a Body Can Be: Disability Justice, the Syllabus, and Academic Labour - Dorrance, Jess; Havard, Julia; Luna, Caleb; Young, Olivia K. (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This article explores the practice of critically and lovingly manifesting access in syllabus construction and examines how axes of oppression shape our classrooms via the syllabus. We are a collective of multi-racial queer and trans disabled academics writing from our personal experiences and our engagements with performance studies and Disability Justice. We argue that the academy must shift from discussions of accommodations to access, surface questions of Disability Justice and teaching labour in graduate school and higher education at large, and offer a series of questions for teachers to examine their approach to disability in their classrooms.